Informal Employment in Era of Asylum: insights from the Second Highest Worldwide Host Country of Refugees - Mahmoud Hailat; Atef Baniata; Sohail Magableh (Migration Letters, 2023)
Purpose: This paper examines the key microeconomic drivers of informal employment in Jordan, the second highest worldwide host country of refugees on per-capita basis. The primary goal is to evaluate the main variables indicating the likelihood of an individual being employed informally; without a contract or social security Design/methodology/approach: Microdata from Jordanian labor market panel surveys performed in 2010 and 2016 and Probit model for binary outcomes is used to assess the influence of a socioeconomic set of variables on the likelihood that an individual works informally. Findings: Between 2010 and 2016, the likelihood of men working in the informal sector increased by almost 10 percentage points. After the post-secondary threshold, education diminishes the likelihood of working informally. The likelihood of being an informal employee was highest among refugee workers, and least common among foreign labors. Public administration and defense, education, water and energy, and health were, in order, the least likely to employ informal labor relative to agricultural, construction, and service sectors. Statistically significant differences in the likelihood of informal employment were found by age group, marital status, and area of residence. Finally, the massive infusion of refugee employees into the labor market raised the proportion of informal employment among refugees, and dropped average wage. Originality/value: Our findings aggravate the challenge for government policies to promote formality in the labor market, to eliminate discrimination, and to bridge the gaps in employment opportunities across labors.